2016
DOI: 10.1155/2016/3818236
|View full text |Cite
|
Sign up to set email alerts
|

Projection of Korean Probable Maximum Precipitation under Future Climate Change Scenarios

Abstract: According to the IPCC Fifth Assessment Report, air temperature and humidity of the future are expected to gradually increase over the current. In this study, future PMPs are estimated by using future dew point temperature projection data which are obtained from RCM data provided by the Korea Meteorological Administration. First, bias included in future dew point temperature projection data which is provided on a daily basis is corrected through a quantile-mapping method. Next, using a scale-invariance techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 13 publications
0
27
0
3
Order By: Relevance
“…The RCM_PMP is identified on the basis of each scenario, then it is compared to the existing PMP value which has been estimated by Lee et al [26], which include the most recent PMP estimates in Korea. As mentioned in the introduction, there are some problems with nationally published reports about PMP.…”
Section: Rcm_pmpmentioning
confidence: 99%
See 3 more Smart Citations
“…The RCM_PMP is identified on the basis of each scenario, then it is compared to the existing PMP value which has been estimated by Lee et al [26], which include the most recent PMP estimates in Korea. As mentioned in the introduction, there are some problems with nationally published reports about PMP.…”
Section: Rcm_pmpmentioning
confidence: 99%
“…As mentioned in the introduction, there are some problems with nationally published reports about PMP. To overcome these problems, Lee et al [26] improved the existing PMP estimation method and calculated the PMP in Korea by applying the latest PMP estimation method suggested by WMO (2009).…”
Section: Rcm_pmpmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies have reported significant changes in extreme precipitation worldwide [1][2][3][4][5][6][7][8][9]. Additionally, it is reported by many studies that the extreme rainfall simulated by global climate models under climate change scenarios change in the future [10][11][12][13][14][15][16]. Since the changes in the extreme rainfalls can alter strategy and policy in water resources as well as design criteria of water-related infrastructures, understanding the change in spatial and temporal variability of rainfall extremes is essential to efficiently managing water resources and preventing the damages from water-related disasters such as floods and landslides.…”
Section: Introductionmentioning
confidence: 99%